Overview Of Land Facilities In The Port Of The Kepok Rasau Jaya Ship Kubu Raya District, West Kalimantan Province - Paulina M Latuheru; Muhammad Khairani; Susan Fadila (IWTJ : International Water Transport Journal, 2021)
The Klotok Rasau Jaya Port is one of the routes that serves passengers from and out of the Kubu Raya Regency to the interior such as Teluk Batang and Padang Tikar. The existence of this route is very important in an effort to support economic development in the West Kalimantan Province. The level of service felt by service users is quite influencing in the implementation of transportation activities, especially the service felt at the port which must comply with the regulations that have been set. The method used to analyze the existing problems is the analysis of the calculation of the need for a passenger waiting room, an analysis of the construction of a counter building for passengers, an analysis of fire fighting facilities, and an analysis of the suitability level of port facilities according to existing conditions. Based on the analysis, it can be concluded that there is no waiting room facility for passengers, causing passengers to often wait on board or in the canteen around the pier, there is no special room for purchasing tickets for passengers, there is no fire fighting facility such as APAR, and it is still not suitable. land facilities based on established regulations.